Effect of tubing length pump on flow derived index during rotary blood pump support - Thananya Khienwad (2018)
© 2017 International Association of Science and Technology for Development - IASTED. The variable of connecting tube length (CTL) in rotary blood pumps (RBPs) is normally existed for the external circulatory support and thus eventually incurs the different outcome as compared to the internal circulatory support. This study aims to determine the effect of the various CTL on the measured parameters from RBP. To serve this purpose, a derived indexes from RBP under mock circulatory loop (MCL) were examined. IQwhich is a slope of the linear regression between the maximal time derivative of pump flow, dQ/dtmax, and its peak to peak, QP2P, was determined to evaluate the effect of 3 different CTLs; 130, 50 and 10 cm (length of inlet tube), and 130, 50 and 50 cm (length of outlet tube). Moreover, the parameters dH/dtmax, which are the maximal time derivative of pressure head (H); AOP-LVP, and its peak to peak were derived. The slope of a linear regression between dQ/dtmaxand dH/dtmaxdecreased during reduce CTL in contrast to IQindex. Thus, this study proved that IQindex was not significant influenced by a hydraulic resistance (including CTL) and therefore can be used to monitor the cardiac function in case of both external and internal RBP support.